Missense variants in ATM in 26,101 breast cancer cases and 29,842 controls - Fletcher, Olivia; Johnson, Nichola; DosSantos Silva, Isabel; Orr, Nick; Ashworth, Alan; Nevanlinna, Heli; Heikkinen, Tuomas; Aittomäki, Kristiina; Blomqvist, Carl; Burwinkel, Barbara; Bartram, Claus R.; Meindl, Alfons; et al. (Cancer epidemiology, biomarkers & prevention, 2010)
Background: Truncating mutations in ATM have been shown to increase the risk of breast cancer but the effect of missense variants remains contentious.Methods: We have genotyped five polymorphic (minor allele frequency, 0.9-2.6%) missense single nucleotide polymorphisms (SNP) in ATM (S49C, S707P, F858L, P1054R, and L1420F) in 26,101 breast cancer cases and 29,842 controls from 23 studies in the Breast Cancer Association Consortium.Results: Combining the data from all five SNPs, the odds ratio (OR) was 1.05 for being a heterozygote for any of the SNPs and 1.51 for being a rare homozygote for any of the SNPs with an overall trend OR of 1.06 (Ptrend = 0.04). The trend OR among bilateral and familial cases was 1.12 (95% confidence interval, 1.02-1.23; Ptrend = 0.02).Conclusions: In this large combined analysis, these five missense ATM SNPs were associated with a small increased risk of breast cancer, explaining an estimated 0.03% of the excess familial risk of breast cancer.Impact: Testing the combined effects of rare missense variants in known breast cancer genes in large collaborative studies should clarify their overall contribution to breast cancer susceptibility. Cancer Epidemiol Biomarkers Prev; 19(9); 2143-51. ©2010 AACR.
Gesehen am 09.12.2024